Slovak-Belarusian trade and economic relations - Ivo Hopta (Проблемы постсоветского пространства)
The article is devoted to the analysis of trade and economic relations between two geographically close European states — Slovakia and Belarus. Special attention is paid to the state and dynamics of Slovak-Belarusian economic relations. Mutual foreign trade between states is considered in detail, including exports and imports. In addition, the author has identified priority structures for goods supplied to these countries.The focus of attention is also focused on the key subjects of the bilateral Slovak-Belarusian economic cooperation, which by their active work make a certain contribution and have a direct impact on the strengthening and expansion of economic contacts between Slovakia and Belarus. The emphasis is also placed on topical and promising projects of Slovak-Belarusian economic cooperation implemented by both states in various fields and areas of interest to both parties. First of all, we are talking about industry, production and cooperation relations and modernization of production; agriculture; energy and waste management; standardization, metrology and conformity assessment; education, science and technology; medicine and pharmaceuticals; tourism.The analysis was also made on the basis of important official documents, materials and resources of the central state authorities of Slovakia and Belarus, as well as quotes of high-ranking political figures of the two states.